Ni(OH)2-CuxO-TiO2 nanocomposite for the enhanced H2 production under solar light: The mechanistic pathway. (6th March 2020) - Subha, N.; Mahalakshmi, M.; Monika, S.; Neppolian, B.
Abstract: The synergistic effect of Ni(OH)2 and Cux O on TiO2 enhanced the H2 production 4 times higher than bare TiO2 at the optimum loading of 1.0 wt% Ni(OH)2 and 0.5 wt% Cux O (1.0 wt% Ni(OH)2 -CT) under natural sunlight. Cux O-TiO2 heterojunctions improved the visible activity and charge transfer efficiency of TiO2 . The layered morphology of non-precious Ni(OH)2 cocatalyst with intercalated H2 O molecules enhanced H2 production by improving the surface charge transfer reaction with additional formation of H + ions through the redox reactions. Based on the characterization and experimental results, the double charge transfer and direct Z-scheme mechanisms were proposed for the charge carrier pathway in Cux O-TiO2 heterojunction. On the whole, the improved visible light response, efficient interfacial charge transfer and production of additional excited free electrons/H + ions enhanced the overall H2 production on Ni(OH)2 -CT, which was also confirmed with various experimental and characterization results. Highlights: Cux O/TiO2 nanocomposites were prepared by simple hydrothermal method. Ni(OH)2 co-catalyst was loaded on Cux O/TiO2 by impregnation method. Heterojunction formed between semiconductors and Ni(OH)2 reduced e − -h + recombination. Direct Z-scheme and double charge transfer mechanisms were discussed.